INNOVATION AND SUSTAINABILITY IN DA’WAH: INTEGRATING CONVENTIONAL AND DIGITAL PRACTICES IN PURWOKERTO - Diki Ramdani; Warto (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
This study explores the transformation of da'wah at Al-Ishlah Mosque in Purwokerto, starting from the crucial issue of the potential discontinuity of traditional da'wah due to digital disruption and generational preference gaps. The objective is to examine how the mosque maintains the continuity of offline da'wah while innovating digitally. Using a qualitative case study with analysis of the Theory of Innovation Diffusion and Media Ecology, the adoption of an adaptive hybrid da'wah model was found. Offline da'wah is maintained as the foundation for conventional congregations, while YouTube embraces the younger generation through visual content. This integration creates hybrid energy that expands reach without eroding tradition. Theoretically, this study offers a framework for cross-generational collaboration and responsive religious institutional innovation.